Neural networks concepts, applications, and implementations - Antognetti, Paolo; Milutinović, Veljko (Prentice Hall advanced reference series. Engineering, 1991)
The basic idea behind this series of books is to combine expertise and experience of contributing authors from a number of different scientific disciplines.